The Impact of Audit Findings on ICS and Compliance with Opinions Government in Lampung - Popy Luky; Einde Evana; Reni Oktavia (PT. Altaf Publishing Corp, 2026)
The Audit Board of the Republic of Indonesia’s (BPK) opinion on Regional Government Financial Statements is a key indicator of accountability in regional financial management and serves as an important governance signal reflecting the quality of public financial oversight. However, several local governments continue to receive an Unqualified Opinion despite findings related to weaknesses in the Internal Control System (ICS) and non-compliance with laws and regulations. This phenomenon is also evident in local governments in Lampung Province, where Unqualified Opinions accompanied by an Emphasis of Matter Paragraph have increased in recent years. This study aims to examine the effect of ICS weaknesses and compliance findings on BPK’s audit opinion. Using a quantitative approach, secondary data were collected from Audit Reports, IHPD, and IHPS for 16 local governments in Lampung Province during 2021–2024, totaling 64 observations. Binary logistic regression analysis shows that ICS weaknesses and non-compliance with laws and regulations negatively and significantly affect BPK’s opinion, both individually and simultaneously, indicating increased governance and fiscal risk concerns.